2018
DOI: 10.1186/s12885-018-4445-z
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in NO- and PGI2- dependent function in aorta in the orthotopic murine model of metastatic 4T1 breast cancer: relationship with pulmonary endothelial dysfunction and systemic inflammation

Abstract: BackgroundPatients with cancer develop endothelial dysfunction and subsequently display a higher risk of cardiovascular events. The aim of the present work was to examine changes in nitric oxide (NO)- and prostacyclin (PGI2)-dependent endothelial function in the systemic conduit artery (aorta), in relation to the formation of lung metastases and to local and systemic inflammation in a murine orthotopic model of metastatic breast cancer.MethodsBALB/c female mice were orthotopically inoculated with 4T1 breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 45 publications
4
25
0
Order By: Relevance
“…As seen in Figure , the greatest variance is found for IR spectra from the micrometastatic (week 3) and macrometastatic phases (week 4), particularly in the 3600‐2800 cm −1 region. This observation could be congruent with the largest variability of a number of metastatic foci present in lungs on weeks 3 and 4 as discussed in our reports . Indeed, it indicates that plasma IR spectra reflect variation in the rate of tumor growth among animals.…”
Section: Resultssupporting
confidence: 92%
“…As seen in Figure , the greatest variance is found for IR spectra from the micrometastatic (week 3) and macrometastatic phases (week 4), particularly in the 3600‐2800 cm −1 region. This observation could be congruent with the largest variability of a number of metastatic foci present in lungs on weeks 3 and 4 as discussed in our reports . Indeed, it indicates that plasma IR spectra reflect variation in the rate of tumor growth among animals.…”
Section: Resultssupporting
confidence: 92%
“…Recent studies utilizing the model of mouse mammary gland cancer 4T1, reflecting a basal-like phenotype (in human: negative for nuclear estrogen receptor (ER) α, progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2), i.e., triple-negative, and positive for epidermal growth factor receptor (EGFR)) [1][2][3][4], have shown a predominant role of endothelium damage during the metastatic process of these cells [5][6][7]. For instance, it is evidenced that endothelial dysfunction in the lungs, which was assessed as decreased activity and phosphorylation of endothelial nitric oxide synthase (eNOS) resulting in a low nitric oxide (NO) production state, was an early event in breast Literature data [4] and our histopathological analyses confirmed that no cancer cells were detected in the lungs of 67NR tumor-bearing mice ( Figure S1A).…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we focused on high definition (HD) and ultra‐high definition (UHD) FTIR spectroscopic imaging of metastatic foci from a murine model of pulmonary metastasis in a 4 T1 carcinoma model of breast cancer, described in detail elsewhere . For this purpose, we used a new optic configuration introduced by Agilent Technologies in its IR microscope which provides additional 5× enhanced magnification.…”
Section: Introductionmentioning
confidence: 99%
“…At this stage, metastasis is mainly defined as macrometastasis—a group of more than 10 cancer cells . On the week five after cancer cells transplantation, the advanced metastatic phase is recognized by extensive metastatic sites as well as progressive leucocytosis and systemic inflammation . Therefore, we aimed here to determine HD and UHD FTIR spectroscopic definition of various metastases developed in different lung locations after inoculation with 4 T1 breast cancer cells at the early and advanced phases.…”
Section: Introductionmentioning
confidence: 99%